2017
DOI: 10.4279/pip.090006
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of water molecules by high energy photons

Abstract: We theoretically study the photoionization of water molecules by high energy photon impact. We develop a model in which the final state wavefunction is given by a Coulomb continuum wavefunction with effective charges and the water molecule bound states are represented using the Moccia's monocentric wavefunctions. We obtain analytical expressions for the transition matrix element that enable the computation of cross sections by numerical quadratures. We compare our predictions for photon energies between 20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The CC wavefunction takes into account the Coulomb interaction of the electron with the residual target in the final channel of the reaction. It has been shown that this interaction must be included to describe the photoionization reaction with neutral targets in the correct manner [20][21][22][23][24].…”
Section: Second-order Time-dependent Perturbation Theorymentioning
confidence: 99%
“…The CC wavefunction takes into account the Coulomb interaction of the electron with the residual target in the final channel of the reaction. It has been shown that this interaction must be included to describe the photoionization reaction with neutral targets in the correct manner [20][21][22][23][24].…”
Section: Second-order Time-dependent Perturbation Theorymentioning
confidence: 99%
“…In figures 4 and 5, we present results for the 3a 1 and 1b 2 orbitals, respectively, that are expected to present three-center interference effects considering their ligand character. As a fact, we observe in figures 4(a) and 5(a) that the molecular cross sections as a function of the energy present deviations from effective atomic ones obtained with the CNDO approximation (17) as the photon energy increases. These differences may be attributed to the coherent emission from the centers of the molecule.…”
Section: Coherent Emission and Interference Effectsmentioning
confidence: 73%
“…The final wavefunction of the CC model (2) takes into account the Coulomb interaction of the electron with the residual target in the final channel of the reaction. It was shown that this interaction must be included for to describe the photoionization reaction with neutral targets in a proper way [1,17,20,21]. The choice Z 1 ef = corresponds to the asymptotic value of the residual target charge at sufficiently large distances from the target.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation